Polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin as well as preparation method and application of polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin
By adopting polyhydroxy crosslinked modified core-shell structure water-based polyurethane/acrylate hybrid resin, the problems of poor flexibility, low tensile strength, weak hydrolysis resistance and high cost are solved, and a high performance and environmentally friendly anti-glare coating is achieved.
Patent Information
- Application Number
- CN202411777507.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Water-based polyurethane coatings have problems such as poor flexibility, low tensile strength, weak hydrolysis resistance and high cost, making it difficult to meet the needs of excellent comprehensive performance.
The polyhydroxy crosslinked modified core-shell structure aqueous polyurethane/acrylate hybrid resin was used to organically combine the aqueous polyurethane and acrylate through seed emulsion polymerization to form core-shell structure nano-microspheres with aqueous polyurethane as the shell and acrylate as the core, and cross-linking and modification was performed using an alcohol crosslinking agent.
It significantly improves the optical and mechanical properties of the coating, enhances the anti-glare effect, improves mechanical properties and hydrolysis resistance, and reduces costs, and is environmentally friendly to the process without the need for adding organic solvents.
Smart Images

Figure CN119751769A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-glare resin, in particular to a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin and a preparation method and application thereof. Background Art
[0002] As the times progress, mobile phones, computers and tablets are becoming more and more popular. People use electronic devices for a long time, resulting in longer and longer viewing time. This long-term use will affect the health of the visual system, especially in strong light environments, where the surface of objects produces strong mirror reflections, resulting in glare, which makes the image blurry when users look at the display or other optical devices, and may even cause visual problems such as temporary blindness. Glare is a serious light pollution that affects or even harms people's daily lives. Common glare hazards include: (1) Building lighting: In modern buildings, most lighting equipment uses LED light sources, which have the characteristics of concentrated light and bright colors, and usually lack reflective covers, resulting in excessive light entering the eyes, which can easily cause direct damage to the eyes. (2) Road traffic: In road traffic, the headlights of cars are bright and have a long illumination distance. At the same time, the lights on both sides of the road and night scene lights will also cause interference. In a dim light environment, the driver's visual ability is likely to decline, and visual fatigue may occur. In severe cases, it may even lead to traffic accidents. (3) Display screens: With the popularization of electronic devices, the frequency of use of display screens is increasing. However, the display screens on the market generally have glare problems. Long-term use can not only easily lead to eye fatigue, but also may cause eye diseases such as myopia and glaucoma. With the improvement of public health awareness, soft and clear surfaces have gradually become a hot topic of research.
[0003] Waterborne polyurethane is widely used to solve the "glare" problem due to its unique gloss properties. The anti-glare mechanism is mainly to form a large number of depressions and undulations on the surface of the substrate (not surface defects), so that after the light is irradiated on the surface of the substrate, the interaction between diffuse reflection and light scattering is enhanced, causing an anti-glare effect. There are two ways to achieve anti-glare with waterborne polyurethane. One is to add physical additives. However, this method is costly and not environmentally friendly and has long been eliminated. The other is to change the inherent properties of waterborne polyurethane itself through chemical modification to achieve an anti-glare effect. This modification can regulate the molecular structure of waterborne polyurethane, so that the material forms a rough microstructure on the surface, thereby achieving a better and more stable anti-glare effect. This method is now used by most people.
[0004] However, waterborne polyurethane still has shortcomings in some properties, such as poor mechanical properties, low chemical resistance, poor hydrolysis resistance and high cost. Acrylate has the advantages of good weather resistance, excellent alkali resistance and low price. Therefore, acrylate modification can well overcome the defects of waterborne polyurethane. On the other hand, the present invention adopts seed emulsion polymerization to organically combine waterborne polyurethane and acrylate, and can form a unique core-shell structure nano microsphere, the structure of this microsphere is to use waterborne polyurethane as shell, acrylate as core, and give it specific physical and chemical properties. The microsphere of this core-shell structure can significantly improve the surface roughness of waterborne polyurethane / acrylate hybrid resin, help to promote the optical property of coating, secondly, it can make emulsion more stable, avoid the generation of phase separation and precipitation phenomenon, in addition, this method can also make the particle size of particle more uniform, effectively enhance the optical property of coating, reach the requirement of anti-glare.
[0005] The cross-linking structure between hybrid polymers also has a great influence on the gloss, water resistance, solvent resistance and mechanical properties of the coating. Therefore, adding a suitable cross-linking agent to form a cross-linking structure can greatly improve the optical and mechanical properties of the coating. One of the most important and practical modification methods for waterborne polyurethane / acrylate hybrid resins is internal cross-linking modification. Commonly used cross-linking agents are mostly alcohols and amine cross-linking agents, such as xylitol, diethylenetriamine, etc. However, amine cross-linking agents have very strict requirements on reaction conditions such as temperature and humidity. At the same time, after cross-linking with amine cross-linking agents, their flexibility is greatly weakened, resulting in easy breakage. In addition, most amine cross-linking agents are highly toxic and irritating, which is very harmful to human health and the environment. In contrast, the reaction conditions of alcohol cross-linking agents are relatively mild, and the reaction speed is moderate and the heat release is less. On the other hand, after cross-linking, a more flexible cross-linking network will be formed, which makes the coating have good flexibility and impact resistance. In addition, many alcohol cross-linking agents are relatively non-toxic or low-toxic, and have no obvious irritating odor. They are suitable as cross-linking agents for internal cross-linking modification of waterborne polyurethane / acrylate hybrid resins. However, we often use frequently used alcohol crosslinking agents, such as trimethylolpropane, and lack the use and research of other alcohol crosslinking agents. Different types of alcohol (such as monohydric alcohol, dihydric alcohol or polyhydric alcohol) crosslinking agents contain different numbers of crosslinking functional groups and different spatial configurations, which will affect the degree of crosslinking reaction and further affect the optical and mechanical properties of the coating. The present invention studies the influence of different types of alcohol crosslinking agents on the optical and mechanical properties of the coating, and finally obtains a multi-hydroxy crosslinked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared by crosslinking modification with xylitol, which has the best optical and mechanical properties.
[0006] Chinese invention patent CN2019101586198 discloses a water-based self-matting acrylate modified polyurethane resin. This technology first prepares an acrylic emulsion containing an amino group, and then mixes it with a blocked polyurethane prepolymer for chain extension reaction. However, a large amount of organic solvent is required in the process of preparing the polyurethane prepolymer, and subsequent treatment will have a great impact on the environment. In addition, since it is difficult to fully physically mix the water-based polyacrylate emulsion with the hydrophobic polyurethane prepolymer, the reaction may be incomplete, and the particle size of the obtained particles is uneven, which affects the performance of the coating.
[0007] Chinese invention patent CN2016108590294 discloses a waterborne polyurethane anti-glare coating material and its preparation method. The technology uses the method of gradual polymerization of waterborne polyurethane prepolymer and two-step chain extension emulsification to prepare waterborne polyurethane anti-glare emulsion, and the resulting layer has both low gloss and high transmittance. However, the use of waterborne polyurethane for preparation is relatively expensive, and the mechanical properties, chemical resistance, hydrolysis resistance and other properties need to be improved, making it difficult to obtain a coating with excellent comprehensive performance. Summary of the invention
[0008] The purpose of the present invention is to solve the defects of waterborne polyurethane coatings such as poor flexibility, low tensile strength, weak hydrolysis resistance and high cost, and to provide an environmentally friendly, comprehensive and excellent anti-glare waterborne polyurethane / acrylate hybrid resin without the need to add organic solvents and having the characteristics of polyhydroxy cross-linking modification and core-shell structure and a preparation method thereof.
[0009] Another object of the present invention is to provide the use of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin in the preparation of anti-glare coatings. The anti-glare coating can be used on the surface of glass substrates and automobile paint films, so that the coating achieves an anti-glare effect.
[0010] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0011] The preparation method of a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin comprises the following steps:
[0012] 1) Under nitrogen protection, dimethylol propionic acid, polyether polyol, xylitol and aliphatic diisocyanate are uniformly mixed, an organic tin catalyst is added, the mixture is reacted at 60-65° C. for 1-1.5 hours, and then the mixture is heated to 80-85° C. for 2-2.5 hours to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0013] 2) adding an unsaturated monomer containing hydroxyl groups to the polyhydroxy cross-linked modified polyurethane prepolymer, cooling to 60-70° C. for reaction for 3-4 hours, and then adding an excess of a compound with a hydroxyl functional group to react to complete the NCO reaction to obtain a carbon-carbon double bond terminated polyurethane prepolymer;
[0014] 3) adding a neutralizing agent to the obtained carbon-carbon double bond terminated polyurethane prepolymer, cooling to 35-45° C. for reaction, and obtaining a polyurethane prepolymer with carboxylate anions;
[0015] 4) adding deionized water to the obtained polyurethane prepolymer with carboxylate anions, stirring at high speed, cooling to room temperature and reacting for 15 to 30 minutes to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0016] 5) Adding acrylate monomers to the obtained polyhydroxy cross-linked modified waterborne polyurethane emulsion, heating to 75-80° C., stirring evenly, adding a free radical initiator to react, and obtaining a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin.
[0017] To further achieve the purpose of the present invention, preferably, the raw materials are used in the following amounts, by mass percentage: 25% to 35% of polyether polyol, 1% to 2% of dimethylol propionic acid, 0.2% to 0.8% of xylitol, 15% to 25% of aliphatic diisocyanate, 0.03% to 0.06% of organic tin catalyst, 5% to 8% of unsaturated monomer containing hydroxyl group, 1.5% to 3% of compound with hydroxyl functional group, 0.6% to 1.4% of neutralizer, 10% to 50% of acrylic monomer, 0.2% to 0.4% of free radical initiator, and the balance is deionized water.
[0018] Preferably, in step 1), the polyether polyol is one or more of polyoxypropylene diol, polyoxypropylene triol and polytetramethylene furan diol; the aliphatic diisocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate and lysine diisocyanate; and the organotin catalyst is one or more of dibutyltin diacetate, dibutyltin dilaurate, stannous octoate and dibutyltin didodecylsulfide.
[0019] Preferably, in step 2), the reaction time of adding an excess of the compound with a hydroxyl functional group is 0.5 to 1 hour; the complete reaction of NCO is controlled by measuring the NCO group content in the prepolymer by the di-n-butylamine method every 0.5 to 1 hour during the reaction.
[0020] Preferably, in step 2), the unsaturated monomer containing a hydroxyl group is one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate; and the compound with a hydroxyl functional group is one or more of n-pentanol, n-butanol and isopropanol.
[0021] Preferably, the reaction time of cooling to 35-45° C. is 0.5-1 h; and the neutralizing agent is one or more of ammonia water, potassium hydroxide, triethylamine, sodium bicarbonate and sodium acetate.
[0022] Preferably, in step 4), the stirring rate of the high-speed stirring is 2000-3000 r / min.
[0023] Preferably, in step 5), the reaction time of adding the free radical initiator is 6 to 7 hours; the acrylic monomer is one or more of methyl methacrylate, butyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate; the free radical initiator is one or more of potassium persulfate, ammonium persulfate and azobisisobutyronitrile; the stirring rate for uniform stirring is 200 to 300 r / min.
[0024] A cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin is prepared by the above preparation method.
[0025] The polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin is used in the preparation of anti-glare coatings. The coatings can be used on any glass substrate surface and automobile paint film to achieve an anti-glare effect.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1) The polyurethane / acrylate hybrid anti-glare resin of the present invention is a nano-microsphere at the microscopic level. The microsphere is a core-shell structure microsphere with water-based polyurethane as the "shell" and acrylate as the "core". The core-shell structure nano-microsphere obtained by seed emulsion polymerization retains the original optical properties of water-based polyurethane and well integrates the excellent weather resistance and alkali resistance of acrylate and its low price into the water-based polyurethane system, so that the coating has better comprehensive performance and price advantage.
[0028] 2) The present invention introduces a hydroxy crosslinking agent to improve the optical and mechanical properties of the coating on the basis of adding acrylate monomers for acrylate modification. Xylitol is a polyhydroxy crosslinking agent, and its hydroxyl group can react with isocyanate. Therefore, the addition of xylitol will cause many crosslinking sites to exist in the system. After high crosslinking, the waterborne polyurethane can better form a dense crosslinked network structure, and the rigidity of the formed latex particles is increased. As the film is prepared by drying, the particle morphology can be better maintained, and the anti-glare performance can be maintained.
[0029] 3) The present invention uses alcohol cross-linking agents for cross-linking modification. This type of cross-linking agent will form a more flexible cross-linked network after cross-linking, so that the coating has good flexibility and impact resistance. At the same time, the reaction conditions are relatively mild, the reaction speed is moderate, and the heat release is less. On the other hand, many alcohol cross-linking agents are relatively non-toxic or low-toxic, have no obvious irritating odor, and have environmental protection and safety values.
[0030] 4) The present invention adopts an aqueous solution seed emulsion polymerization method, does not add any organic reagents, and does not require subsequent removal of organic solvents from the product, which is very environmentally friendly and energy-saving.
[0031] 5) In the process of preparing the emulsion, the present invention adopts a high-speed stirrer at a speed of 2000r / min to stir at high speed, so that nanoparticles with a particle size of 300-800nm can be prepared, and the anti-glare requirements can be met without adding any additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is an infrared spectrum of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention.
[0033] Figure 2 This is a particle size distribution diagram of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention.
[0034] Figure 3 This is a scanning electron microscope (SEM) image of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention.
[0035] Figure 4 This is the stress-strain curve of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention.
[0036] Figure 5 This is a transmittance graph of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention.
[0037] Figure 6 This is a transmission electron microscope (TEM) image of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments do not limit the scope of protection claimed for the present invention.
[0039] The present invention introduces a hydroxy crosslinking agent to improve the optical and mechanical properties of the coating, so the preparation of the polyhydroxy crosslinked modified polyurethane prepolymer is to mix dimethylol propionic acid, polyether polyol, xylitol and aliphatic diisocyanate uniformly under nitrogen protection, and add an organic tin catalyst to react to obtain; wherein xylitol contains a large amount of hydroxyl groups, which can react with isocyanate, and after adding xylitol, there will be many crosslinking sites in the system for crosslinking modification with waterborne polyurethane, and after high crosslinking, the waterborne polyurethane as an external "shell" will form a dense crosslinking network, so that the particles are closely stacked, resulting in an increase in the rigidity of the formed latex particles, and the waterborne polyurethane can better wrap acrylate to form more uniform nano-microspheres, and as the coating is prepared, the particle morphology can be better maintained. When light is irradiated on the surface of the glass plate coated with the coating, due to the presence of these rough structures, most of the light will be diffusely reflected and refracted, and only a small part will be directly reflected to the human eye, effectively reducing the glossiness of the coating surface, reflecting a good anti-glare ability.
[0040] The preparation method of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin of the present invention is characterized by comprising the following steps:
[0041] 1) Under nitrogen protection, dimethylol propionic acid, polyether polyol, xylitol and aliphatic diisocyanate are uniformly mixed, an organic tin catalyst is added, the mixture is reacted at 60-65° C. for 1-1.5 hours, and then the mixture is heated to 80-85° C. for 2-2.5 hours to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0042] 2) adding an unsaturated monomer containing hydroxyl groups to the polyhydroxy cross-linked modified polyurethane prepolymer, cooling to 60-70° C. for reaction for 3-4 hours, and then adding an excess of a compound with a hydroxyl functional group to react to complete the NCO reaction to obtain a carbon-carbon double bond terminated polyurethane prepolymer;
[0043] 3) adding a neutralizing agent to the obtained carbon-carbon double bond terminated polyurethane prepolymer, cooling to 35-45° C. for reaction, and obtaining a polyurethane prepolymer with carboxylate anions;
[0044] 4) adding deionized water to the obtained polyurethane prepolymer with carboxylate anions, stirring at high speed, cooling to room temperature and reacting for 15 to 30 minutes to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0045] 5) Adding acrylate monomers to the obtained polyhydroxy cross-linked modified waterborne polyurethane emulsion, heating to 75-80° C., stirring evenly, adding a free radical initiator to react, and obtaining a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin.
[0046] The polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin prepared by the present invention has a core-shell structure with polyurethane as the shell and acrylate as the core; and a polyhydroxy cross-linking agent is used to cross-link and modify the waterborne polyurethane, so that the waterborne polyurethane as the "shell" is highly cross-linked, the rigidity of the formed latex particles is increased, and the film-forming maintains good anti-glare performance.
[0047] The test descriptions involved in the embodiments are as follows:
[0048] 1) Coating preparation method: According to GB / T 1727-2021 standard, the prepared anti-glare waterborne polyurethane / acrylate hybrid emulsion was coated on a glass substrate with an RDS linear coating rod, and the film thickness was (35±5) μm. It was then placed in a 40°C digital display high-temperature drying oven for 24 hours, then taken out and cooled, and placed in a drying dish for later use.
[0049] 2) Coating gloss: According to ISO / 2813 standard, glass is used as the coating substrate and a 500MC gloss meter from Erichsen of Germany is used to measure the 60° gloss of the coating.
[0050] 3) Emulsion particle size: The hybrid emulsion was tested using a LA-960V2 laser particle size distribution analyzer. The emulsion was diluted with deionized water to a solid content of about 1 wt %, and then added dropwise into the sample pool.
[0051] 4) Mechanical properties of coating films: After the coating films were cut according to GB / T 528-2009, the mechanical properties were tested on a UT-2080 tensile testing machine at a tensile rate of 200 mm / min.
[0052] 5) Water absorption: The coating is tested according to HG / T 3344-2012. Take an appropriate amount of dry coating and weigh it, and record the weight as W1. Soak the coating in excess deionized water until constant weight, then take out the sample and wipe the moisture on the surface of the sample with absorbent paper, and record the sample weight at this time as W2. Water absorption (W a ) is calculated as follows:
[0053]
[0054] 6) Light transmittance: Using a blank glass substrate as a reference sample, the light transmittance of the coating film applied on the transparent glass substrate was tested using a UV-3600 ultraviolet-visible absorption spectrometer with a scanning range of 350-800nm.
[0055] 7) Pencil hardness: The hardness of the coating film is measured according to the pencil method for paints and varnishes GB / T6739-2006.
[0056] Example 1
[0057] 1) Under nitrogen protection, 2.73 g of dimethylol propionic acid, 62.8 g of polytetrahydrofuran diol, 0.95 g of xylitol and 39.55 g of isophorone diisocyanate were placed in a constant temperature water bath and mixed evenly, 0.06 g of dibutyltin dilaurate was added and reacted at 60° C. for 1 h, and then the temperature was raised to 80° C. and reacted for 2.5 h to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0058] 2) adding 12.87 g of hydroxyethyl acrylate to the polyhydroxy cross-linked modified polyurethane prepolymer obtained in step 1), cooling to 65° C. and reacting for 3 h, determining the NCO group content in the prepolymer by the di-n-butylamine method every 1 h during the reaction, and then adding 3.52 g of n-butanol and reacting for 1 h to ensure that the final NCO reaction is complete, thereby obtaining a carbon-carbon double bond terminated polyurethane prepolymer;
[0059] 3) adding 2.06 g of triethylamine to the carbon-carbon double bond terminated polyurethane prepolymer obtained in step 2) for neutralization, cooling to 35° C. and reacting for 0.5 h to obtain a polyurethane prepolymer with carboxylate anions;
[0060] 4) Slowly adding 476.01 g of deionized water to the polyurethane prepolymer with carboxylate anions obtained in step 3), stirring at a high speed of 3000 r / min, cooling to room temperature and reacting for 30 min to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0061] 5) Add 80.01 g of methyl methacrylate to the aqueous polyurethane emulsion obtained in step 4), raise the temperature to 75° C., stir evenly at a stirring rate of 200 r / min, and then add 0.46 g of azobisisobutyronitrile to react for 6 hours to obtain a polyhydroxy cross-linked modified core-shell structure aqueous polyurethane / acrylate hybrid anti-glare emulsion.
[0062] 6) The emulsion obtained in step 5) is evenly coated on a glass slide using an RDS linear coating rod, placed in a 40°C high-temperature drying oven for 24 hours, taken out and cooled and placed in a drying dish to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare coating. After testing, the average particle size is 510nm, the tensile strength is 22.31MPa, and the transmittance is above 82% in the entire band.
[0063] Figure 1 This is the infrared spectrum of the multi-hydroxy cross-linked modified core-shell waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. In the system, -NCO reacts with -OH to form a carbamate group. -1 and 1740cm -1 The absorption peaks at 2940cm correspond to the stretching vibration peaks of the NH bond and C=O bond in the group. -1 and 2860cm -1 The absorption peak at 2260cm-1 is attributed to the stretching vibration peak of the CH bond of CH3 and CH2 in the waterborne polyurethane / acrylate hybrid coating. The antisymmetric stretching vibration peak and symmetric stretching vibration peak of COC on the main chain of the molecule are located at 1240cm-1 and 1110cm-1 respectively. It is worth noting that the corresponding characteristic peak of -NCO at 2260cm-1 did not appear, and the broad peak of -OH at high wavenumber did not appear, all of which indicate that the -OH and -NCO in the system reacted completely, and the waterborne polyurethane / acrylate hybrid anti-glare coating was successfully prepared.
[0064] Figure 2 The particle size distribution diagram of the multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. This example successfully synthesized the hybrid emulsion with core-shell structure nano-microspheres through three steps of step polymerization, seed emulsion polymerization and free radical polymerization. It can be seen from the figure that the particle size distribution is 200nm-800nm, the average particle size is 510nm, and the particles all meet the nano-level requirements. Therefore, after the emulsion is made into a coating film, it is scraped on a glass plate to form a rough surface at the microscopic level on the glass plate, so that the anti-glare requirements are met.
[0065] Figure 3 This is a SEM image of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. The waterborne polyurethane / acrylate hybrid emulsion prepared in this example has nano-scale particles with an average particle size of 510 nm. After the emulsion is scraped onto a glass plate to form a coating and dried, the coating can still retain the original particle size and core-shell structure, forming a microscopically rough surface. Figure 3 The rough structure of the coating's microscopic surface can be seen more intuitively, and each particle is spherical, proving the existence of nano-microspheres.
[0066] Figure 4This is the stress-strain curve of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. As can be seen from the figure, the tensile strength can reach up to 22.31 MPa, which is due to the use of polyhydroxy cross-linking agents to enhance the stability of particles in the waterborne polyurethane hybrid emulsion, and the higher cross-linking density makes the particles densely packed in the aqueous medium, so that the particles have a more uniform arrangement, and the stress transfer between the molecular chains is enhanced, so that the coating has excellent mechanical properties.
[0067] Figure 5 This is a transmittance image of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. The emulsion obtained in this example was evenly scraped on a glass plate, and its transmittance to light was measured using an ultraviolet spectrophotometer. It is not difficult to find from the figure that the transmittance of the coating film in the full scanning range is still more than 82%, and the coating film has a relatively high transmittance.
[0068] Figure 6 TEM image of the polyhydroxy cross-linked modified core-shell waterborne polyurethane / acrylate hybrid anti-glare resin obtained in Example 1. The difference in hydrophilic and hydrophobic abilities of the polyurethane and acrylate blocks enables the molecular chains to self-assemble into latex particles with a "core-shell structure" after emulsification and free radical polymerization. It can be found from the figure that the hydrophobic acrylate is distributed inside the particle as the "core", and the hydrophilic polyurethane is distributed in the outer layer of the particle as the "shell" that wraps the acrylate. Therefore, the principle analysis of the polymerization reaction and the results of the projection electron microscope prove that the waterborne polyurethane / acrylate hybrid emulsion with a core-shell structure has been successfully prepared.
[0069] The infrared spectrum, particle size distribution, stress-strain diagram, transmittance diagram and electron microscope diagram of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin obtained in the following examples are all consistent with Figure 1-6 They are basically the same, so they are not listed here one by one.
[0070] Example 2
[0071] 1) Under nitrogen protection, 3.15 g of dimethylol propionic acid, 72.5 g of polytetrahydrofuran diol, 0.36 g of xylitol and 45.65 g of isophorone diisocyanate were placed in a constant temperature water bath and mixed evenly, 0.04 g of dibutyltin diacetate was added and reacted at 63° C. for 1 h, and then the temperature was raised to 83° C. and reacted for 2 h to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0072] 2) adding 16.80 g of hydroxyethyl methacrylate to the polyurethane prepolymer obtained in step 1), cooling to 70° C. and reacting for 3.5 h, determining the NCO group content in the prepolymer by the di-n-butylamine method every 0.5 h during the reaction, and then adding 4.60 g of n-pentanol and reacting for 1 h to ensure that the final NCO reaction is complete, thereby obtaining a polyurethane prepolymer terminated with a carbon-carbon double bond;
[0073] 3) adding 2.38 g of sodium bicarbonate to the carbon-carbon double bond terminated polyurethane prepolymer obtained in step 2) for neutralization, cooling to 40° C. and reacting for 1 h to obtain a polyurethane prepolymer with carboxylate anions;
[0074] 4) slowly adding 558.37 g of deionized water to the polyurethane prepolymer with carboxylate anions obtained in step 3), stirring at a high speed of 2500 r / min, cooling to room temperature and reacting for 20 min to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0075] 5) Add 93.66 g of butyl acrylate to the polyhydroxy cross-linked modified waterborne polyurethane emulsion obtained in step 4), heat to 78° C., stir evenly at a stirring rate of 250 r / min, then add 0.55 g of potassium persulfate and react for 7 h to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare emulsion.
[0076] 6) The emulsion obtained in step 5) is evenly coated on a glass slide using an RDS linear coating rod, placed in a 40°C high-temperature drying oven for 24 hours, taken out and cooled and placed in a drying dish to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare coating. After testing, the average particle size is 371nm, the tensile strength is 17.33MPa, and the transmittance is above 87% in the entire band.
[0077] Example 3
[0078] 1) Under nitrogen protection, 2.80 g of dimethylol propionic acid, 64.3 g of polyoxypropylene glycol, 0.65 g of xylitol and 40.49 g of hexamethylene diisocyanate were placed in a constant temperature water bath and mixed evenly, 0.05 g of an organic tin catalyst was added and reacted at 65° C. for 1.5 h, and then the temperature was raised to 85° C. and reacted for 2 h to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0079] 2) adding 14.04 g of hydroxypropyl acrylate to the polyurethane prepolymer obtained in step 1), cooling to 60° C. and reacting for 4 h, determining the NCO group content in the prepolymer by the di-n-butylamine method every 1 h during the reaction, and then adding 3.84 g of isopropanol and reacting for 1 h to ensure that the final NCO reaction is complete, thereby obtaining a polyurethane prepolymer terminated with a carbon-carbon double bond;
[0080] 3) adding 2.11 g of sodium acetate to the carbon-carbon double bond terminated polyurethane prepolymer obtained in step 2) for neutralization, cooling to 30° C. and reacting for 1 h to obtain a polyurethane prepolymer with carboxylate anions;
[0081] 4) Slowly adding 491.30 g of deionized water to the polyurethane prepolymer with carboxylate anions obtained in step 3), stirring at a high speed of 2000 r / min, cooling to room temperature and reacting for 20 min to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0082] 5) Add 82.49 g of 2-methyl methacrylate to the aqueous polyurethane emulsion obtained in step 4), raise the temperature to 80° C., stir evenly at a stirring rate of 300 r / min, then add 0.48 g of ammonium persulfate and react for 6.5 h to obtain a polyhydroxy cross-linked modified core-shell structure aqueous polyurethane / acrylate hybrid anti-glare emulsion.
[0083] 6) The emulsion obtained in step 5) is evenly coated on a glass slide using an RDS linear coating rod, placed in a 40°C high-temperature drying oven for 24 hours, taken out and cooled and placed in a drying dish to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare coating. After testing, the average particle size is 457nm, the tensile strength is 18.94MPa, and the transmittance is above 85% in the entire band.
[0084] Example 4
[0085] 1) Under nitrogen protection, 2.99 g of dimethylol propionic acid, 68.6 g of polyoxypropylene triol, 1.38 g of xylitol and 43.20 g of lysine diisocyanate were placed in a constant temperature water bath and mixed evenly, 0.04 g of an organic tin catalyst was added and reacted at 60° C. for 1.5 h, and then the temperature was raised to 83° C. and reacted for 2.5 h to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0086] 2) adding 13.14 g of hydroxypropyl methacrylate to the polyurethane prepolymer obtained in step 1), cooling to 70° C. and reacting for 3 h, determining the NCO group content in the prepolymer by the di-n-butylamine method every 1 h during the reaction, and then adding 3.59 g of n-pentanol and reacting for 0.5 h to ensure that the final NCO reaction is complete, thereby obtaining a polyurethane prepolymer terminated with a carbon-carbon double bond;
[0087] 3) adding 2.25 g of sodium bicarbonate to the carbon-carbon double bond terminated polyurethane prepolymer obtained in step 2) for neutralization, cooling to 40° C. and reacting for 0.5 h to obtain a polyurethane prepolymer with carboxylate anions;
[0088] 4) Slowly adding 515.79 g of deionized water to the polyurethane prepolymer with carboxylate anions obtained in step 3), stirring at a high speed of 2600 r / min, cooling to room temperature and reacting for 15 min to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0089] 5) Add 86.78 g of ethyl 2-methacrylate to the aqueous polyurethane emulsion obtained in step 4), raise the temperature to 76° C., stir evenly at a stirring rate of 200 r / min, and then add 0.50 g of azobisisobutyronitrile and react for 7 hours to obtain a polyhydroxy cross-linked modified core-shell structure aqueous polyurethane / acrylate hybrid anti-glare emulsion.
[0090] 6) The emulsion obtained in step 5) is evenly coated on a glass slide using an RDS linear coating rod, placed in a 40°C high-temperature drying oven for 24 hours, taken out and cooled and placed in a drying dish to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare coating. After testing, the average particle size is 735nm, the tensile strength is 23.23MPa, and the transmittance is above 80% in the entire band.
[0091] Example 5
[0092] 1) Under nitrogen protection, 2.86 g of dimethylol propionic acid, 65.7 g of polytetrahydrofuran diol, 1.65 g of xylitol and 41.37 g of isophorone diisocyanate were placed in a constant temperature water bath and mixed evenly, 0.07 g of an organic tin catalyst was added and reacted at 60° C. for 1.5 h, and then the temperature was raised to 80° C. and reacted for 2 h to obtain a polyhydroxy cross-linked modified polyurethane prepolymer;
[0093] 2) adding 11.70 g of hydroxyethyl acrylate to the polyurethane prepolymer obtained in step 1), cooling to 65° C. and reacting for 4 h, determining the NCO group content in the prepolymer by the di-n-butylamine method every 1 h during the reaction, and then adding 3.20 g of n-butanol and reacting for 0.5 h to ensure that the final NCO reaction is complete, thereby obtaining a polyurethane prepolymer terminated with a carbon-carbon double bond;
[0094] 3) adding 2.16 g of triethylamine to the carbon-carbon double bond terminated polyurethane prepolymer obtained in step 2) for neutralization, cooling to 45° C. and reacting for 0.5 h to obtain a polyurethane prepolymer with carboxylate anions;
[0095] 4) Slowly adding 489.98 g of deionized water to the polyurethane prepolymer with carboxylate anions obtained in step 3), stirring at a high speed of 2800 r / min, cooling to room temperature and reacting for 30 min to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion;
[0096] 5) Add 82.53 g of methyl methacrylate to the aqueous polyurethane emulsion obtained in step 4), heat to 75° C., stir evenly at a stirring rate of 300 r / min, then add 0.47 g of azobisisobutyronitrile and react for 6.5 h to obtain a polyhydroxy cross-linked modified core-shell structure aqueous polyurethane / acrylate hybrid anti-glare emulsion.
[0097] 6) The emulsion obtained in step 5) is evenly coated on a glass slide using an RDS linear coating rod, placed in a 40°C high-temperature drying oven for 24 hours, taken out and cooled and placed in a drying dish to obtain a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare coating. After testing, the average particle size is 816nm, the tensile strength is 23.73MPa, and the transmittance is above 75% in the entire band.
[0098] Table 1
[0099]
[0100] As can be seen from the data in Table 1, the polyhydroxy cross-linked modified core-shell waterborne polyurethane / acrylate hybrid anti-glare resin prepared by xylitol in the present invention has excellent anti-glare performance and other comprehensive properties. The polyhydroxy cross-linked modified core-shell waterborne polyurethane / acrylate hybrid anti-glare coatings obtained in Examples 1-5 have a transmittance of at least 75% in the full scanning band, have excellent transmittance, tensile strength of more than 17 MPa, pencil hardness of more than H, and water absorption of less than 11.2%.
[0101] Moreover, the reaction process of the present invention does not use any organic solvents at all, which is green and environmentally friendly; the raw materials used are simple and easy to obtain, and the overall process is simple and easy to operate. Although waterborne polyurethane itself is often used to prepare anti-glare coatings, its own problems such as poor mechanical properties, poor hydrolysis resistance and high cost cannot be ignored. Therefore, the acrylate modification and polyhydroxy cross-linking modification adopted in the present invention can effectively improve these defects and make the anti-glare ability more excellent. The hybrid emulsion obtained by the present invention has nano-scale core-shell structured microspheres, which can form a microscopic rough surface in the film-forming process to achieve anti-glare ability, and can also ensure a high light transmittance, so that this coating can be applied on the surface of substrates in many fields, broadening its application scenarios.
[0102] The present invention prepares a multi-hydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin, which can be used in any coating field such as decorative coatings, industrial coatings and architectural coatings, and has a wide range of application scenarios. Compared with the existing anti-glare waterborne polyurethane, the present invention, on the basis of having the basic performance of anti-glare, also improves the shortcomings of waterborne polyurethane such as poor mechanical properties, low hardness, poor hydrolysis resistance, high cost and the need to use a large amount of solvents in the preparation process, and at the same time makes the coating have good light transmittance, so that it can be applied to mirror surfaces such as glass, broadening its application field. On the other hand, the present invention prepares a nano-scale hybrid resin with a core-shell structure, and constructs a microscopic rough surface through the accumulation of nanoparticles, which can meet the anti-glare requirements, and at the same time improves the problems of low gloss and low light transmittance of the existing waterborne polyurethane / acrylate hybrid resin.
Claims
1. A method for preparing a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin, characterized in that The following steps are involved: 1) Under nitrogen protection, dimethylol propionic acid, polyether polyol, xylitol and aliphatic diisocyanate are uniformly mixed, an organic tin catalyst is added, the mixture is reacted at 60-65° C. for 1-1.5 hours, and then the mixture is heated to 80-85° C. for 2-2.5 hours to obtain a polyhydroxy cross-linked modified polyurethane prepolymer; 2) adding an unsaturated monomer containing hydroxyl groups to the polyhydroxy cross-linked modified polyurethane prepolymer, cooling to 60-70° C. for reaction for 3-4 hours, and then adding an excess of a compound with a hydroxyl functional group to react to complete the NCO reaction to obtain a carbon-carbon double bond terminated polyurethane prepolymer; 3) adding a neutralizing agent to the obtained carbon-carbon double bond terminated polyurethane prepolymer, cooling to 35-45° C. for reaction, and obtaining a polyurethane prepolymer with carboxylate anions; 4) adding deionized water to the obtained polyurethane prepolymer with carboxylate anions, stirring at high speed, cooling to room temperature and reacting for 15 to 30 minutes to obtain a polyhydroxy cross-linked modified waterborne polyurethane emulsion; 5) Adding acrylate monomers to the obtained polyhydroxy cross-linked modified waterborne polyurethane emulsion, heating to 75-80° C., stirring evenly, adding a free radical initiator to react, and obtaining a polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin.
2. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: Calculated in percentage by mass, the dosage of the raw materials is: 25% to 35% of polyether polyol, 1% to 2% of dimethylol propionic acid, 0.2% to 0.8% of xylitol, 15% to 25% of aliphatic diisocyanate, 0.03% to 0.06% of organic tin catalyst, 5% to 8% of unsaturated monomer containing hydroxyl group, 1.5% to 3% of compound with hydroxyl functional group, 0.6% to 1.4% of neutralizer, 10% to 50% of acrylic monomer, 0.2% to 0.4% of free radical initiator, and the balance is deionized water.
3. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: In step 1), the polyether polyol is one or more of polyoxypropylene diol, polyoxypropylene triol and polytetramethylene furan diol; the aliphatic diisocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate and lysine diisocyanate; the organotin catalyst is one or more of dibutyltin diacetate, dibutyltin dilaurate, stannous octoate and dibutyltin didodecylsulfide.
4. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: In step 2), the reaction time of adding an excess of the compound with a hydroxyl functional group is 0.5 to 1 hour; the complete reaction of NCO is controlled by measuring the NCO group content in the prepolymer by the di-n-butylamine method every 0.5 to 1 hour during the reaction.
5. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: In step 2), the unsaturated monomer containing a hydroxyl group is one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate; and the compound with a hydroxyl functional group is one or more of n-pentanol, n-butanol and isopropanol.
6. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: In step 3), the reaction time of cooling to 35-45° C. is 0.5-1 h; the neutralizing agent is one or more of ammonia water, potassium hydroxide, triethylamine, sodium bicarbonate and sodium acetate.
7. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 1, characterized in that: In step 4), the stirring rate of the high-speed stirring is 2000-3000 r / min.
8. The method for preparing the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 2, characterized in that: In step 5), the reaction time of adding the free radical initiator is 6 to 7 hours; the acrylic monomer is one or more of methyl methacrylate, butyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate; the free radical initiator is one or more of potassium persulfate, ammonium persulfate and azobisisobutyronitrile; the stirring rate for uniform stirring is 200 to 300 r / min.
9. A cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the polyhydroxy cross-linked modified core-shell structure waterborne polyurethane / acrylate hybrid anti-glare resin according to claim 9 in the preparation of anti-glare coatings.
Citation Information
Patent Citations
Water-based polyurethane anti-glare coating material and preparation method thereof
CN106380569A
Self-repairing anti-glare waterborne polyurethane paint and preparation method thereof
CN106867388A
Waterborne acrylic modified polyurethane hybrid resin prepared by solvent-free method
CN107446457A
Wear-resistant waterborne polyurethane matting coating material, preparation method and application thereof
CN113105815A
Waterborne polyurethane / acrylate hybrid matting coating with core-shell structure as well as preparation method and application of waterborne polyurethane / acrylate hybrid matting coating
CN116333552A